In vitro and in vivo activities of a novel β-lactamase inhibitor combination imipenem/XNW4107 against recent clinical Gram-negative bacilli from China - Yun Li; Mengyao Yan; Feng Xue; Wei Zhong; Xiao Liu; Xi Chen; Yuchuan Wu; Jia Zhang; Qing Wang; Bo Zheng; Yuan Lv (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Objectives: XNW4107 is a novel β-lactamase inhibitor that possesses broad activity against serine-β-lactamases. XNW4107 in combination with imipenem exhibited potent in vitro activity against carbapenem-resistant bacteria and particularly against carbapenem-resistant Acinetobacter baumannii. This study aimed to evaluate the in vitro and in vivo antibacterial activities of imipenem/XNW4107. Methods: The minimum inhibitory concentrations, minimum bactericidal concentrations, time-kill curves, post-antibiotic effects, and spontaneous frequency of resistance were used to investigate the imipenem/XNW4107 in vitro activity. A mouse systemic infection model was used to evaluate the imipenem/XNW4107 in vivo efficacy. Results: MIC90 of imipenem/XNW4107 against imipenem-nonsusceptible A. baumannii (n = 106) was 8 mg/L, which was 16-fold lower than the MIC90 of imipenem; the resistance rate decreased from 90% to 20% applying the CLSI imipenem breakpoint. MIC90 of imipenem/XNW4107 against imipenem-resistant Klebsiella pneumoniae (n = 54) was 2 mg/L, which was 128-fold lower than the MIC90 of imipenem; 80% imipenem-nonsusceptible Pseudomonas aeruginosa (n = 101) exhibited MICs of imipenem/XNW4107 from 2 to 8 mg/L, which were 4- to 8-fold lower than the MICs of imipenem. Imipenem/XNW4107 was bactericidal against A. baumannii, K. pneumoniae, and Escherichia coli. The time-kill curves showed that increasing concentrations did not result in progressively increased killing at concentrations >4 × MIC. Imipenem/XNW4107 has a low potential for resistance development in tested strains except for K. pneumoniae. Imipenem/XNW4107 provided good protection against imipenem-resistant A. baumannii and K. pneumoniae in vivo. Conclusions: The broad-spectrum profile and potent in vitro and in vivo antibacterial activities support imipenem/XNW4107 as a promising investigational candidate.